Integral Powers of a Complex Number

Integral power of a complex number is also a complex number. In other words any integral power of a complex number can be expressed in the form of A + iB, where A and B are real.

If z is any complex number, then positive integral powers of z are defined as z\(^{1}\) = a, z\(^{2}\) = z z, z\(^{3}\) = z\(^{2}\) z, z\(^{4}\) = z\(^{3}\) z and so on.

If z is any non-zero complex number, then negative integral powers of z are defined as:

z\(^{-1}\) = \(\frac{1}{z}\), z\(^{-2}\) = \(\frac{1}{z^{2}}\), z\(^{-3}\) = \(\frac{1}{z^{3}}\), etc.

If z ≠ 0, then z\(^{0}\) = 1.


Integral Power of:

Any integral power of i is i or, (-1) or 1.

Integral power of i are defined as:

i\(^{0}\) = 1, i\(^{1}\) = i, i\(^{2}\) = -1,

i\(^{3}\) = i\(^{2}\) i = (-1)i = -i,

i\(^{4}\) = (i\(^{2}\))\(^{2}\) = (-1)\(^{2}\) = 1,

i\(^{5}\) = i\(^{4}\) i = 1 i = i,

i\(^{6}\) = i\(^{4}\) i\(^{2}\) = 1 (-1) = -1, and so on.

i\(^{-1}\) = \(\frac{1}{i}\) = \(\frac{1}{i}\) × \(\frac{i}{i}\) = \(\frac{i}{-1}\) = - i

Remember that \(\frac{1}{i}\) = - i

i\(^{-1}\) = \(\frac{1}{i^{2}}\) = \(\frac{1}{-1}\) = -1

i\(^{-3}\) = \(\frac{1}{i^{3}}\) = \(\frac{1}{i^{3}}\) × \(\frac{i}{i}\) = \(\frac{i}{i^{4}}\) = \(\frac{i}{1}\) = i

i\(^{-4}\) = \(\frac{1}{i^{4}}\) = \(\frac{1}{1}\) = 1, and so on.

Note that i\(^{4}\) = 1 and i\(^{-4}\) = 1. It follows that for any integer k,

i\(^{4k}\) = 1, i\(^{4k + 1}\)= i, i\(^{4k + 2}\) = -1, i\(^{4k + 3}\) = - i.


Solved examples on integral powers of a complex number:

1. Express i\(^{109}\) in the form of a + ib.

Solution:

i\(^{109}\)

= i\(^{4 × 27 + 1}\)

= i, [Since, we know that for any integer k, i\(^{4k + 1}\) = i]

= 0 + i, which is the required form of a + ib.


2. Simplify the expression i\(^{35}\) + \(\frac{1}{i^{35}}\) in the form of a + ib.

Solution:

i\(^{35}\) + \(\frac{1}{i^{35}}\)

= i\(^{35}\) + i\(^{-35}\)

= i\(^{4 × 8 + 3}\) + i\(^{4 × (-9) + 1}\)

= 0 + 0

= 0

= 0 + i0, which is the required form of a + ib.


3. Express (1 - i)\(^{4}\) in the standard form a + ib.

Solution:

(1 - i)\(^{4}\)

= [(1 - i)\(^{2}\)]\(^{2}\)

= [1 + i\(^{2}\) - 2i]\(^{2}\)

= (1 + (-1) – 2i)\(^{2}\)

= (-2i)\(^{2}\)

= 4i\(^{2}\)

= 4(-1)

= -4

= -4 + i0, which is the required standard form a + ib.




11 and 12 Grade Math 

From Integral Powers of a Complex Number to HOME PAGE




Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.